The SAGE Encyclopedia of Classroom Management 2014
DOI: 10.4135/9781483346243.n80
|View full text |Cite
|
Sign up to set email alerts
|

Co-Teaching for Inclusive Classrooms

Abstract: The purpose of this qualitative Research Project is to explore what strategies general education and special education teachers used to support students in a co-taught inclusive classroom environment. The primary research question that informs this study is: How does a sample of general education and special education elementary school teachers who work in inclusive classrooms effectively co-teach within their assigned co-taught subjects in order to support the learning needs and learning style preferences of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
(37 reference statements)
0
1
1
Order By: Relevance
“…In terms of specific coteaching models, teachers can consider their instructional goals when selecting when and how much of a co-teaching model is appropriate to utilize and which teacher would be most appropriate to lead instruction. The overall goal is that students benefit from the expertise of both teachers (Scruggs et al, 2007), but that is not what we observed. Teachers spent a majority of time using a co-teaching model characterized by one teacher, primarily the CAT, leading instruction (e.g., one teach-one assist).…”
Section: Instructional Delivery Practices In Co-taught Ela Classroomscontrasting
confidence: 61%
See 1 more Smart Citation
“…In terms of specific coteaching models, teachers can consider their instructional goals when selecting when and how much of a co-teaching model is appropriate to utilize and which teacher would be most appropriate to lead instruction. The overall goal is that students benefit from the expertise of both teachers (Scruggs et al, 2007), but that is not what we observed. Teachers spent a majority of time using a co-teaching model characterized by one teacher, primarily the CAT, leading instruction (e.g., one teach-one assist).…”
Section: Instructional Delivery Practices In Co-taught Ela Classroomscontrasting
confidence: 61%
“…Several types of co-teaching models exist (e.g., team-teaching, parallel teaching, one teach–one assist; Murawski & Dieker, 2004). Although the literature does not recommend spending a specific amount of time on any one co-teaching model, the assumption is that students will benefit from models that capitalize on the expertise of both teachers (e.g., team teaching; Scruggs, Mastropieri, & McDuffie, 2007). Furthermore, certain co-teaching models allow SETs to play a strong instructional role in the classroom by allowing teachers to provide small-group, differentiated instruction (e.g., station teaching) rather than having one teacher dominate instruction while the other assists.…”
Section: Co-teaching: a Promising Service Delivery Model?mentioning
confidence: 99%